The Influence of Celebrity Endorser and Brand Image on Purchase Intention of Whitelab Products in Bandar Lampung - Rini, Desak Putu Ayu Setya; Sari, Aida (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
In the digital era, social media has become an effective promotional tool to build brand image and reach consumers widely. Celebrity endorsers are used as a marketing strategy to increase the appeal and credibility of a product, while brand image reflects consumer perceptions of a brand that can influence purchasing decisions. The purpose of this study was to analyze the influence of celebrity endorsers and brand image on the intention to purchase Whitelab products in Bandar Lampung. This study uses a quantitative method with primary data collected through a questionnaire. The sample in this study was 130 respondents collected with the help of a questionnaire. The analysis methods used in this study are validity testing, reliability testing, and using multiple linear regression, and hypothesis testing, namely the t-test, and the F-test. The results of the study indicate that both celebrity endorsers and brand image have a significant influence on consumer purchase intentions. The credibility, appeal, and expertise of celebrity endorsers, as well as a strong brand reputation, have been shown to contribute to increasing consumer purchase intentions for Whitelab products.